Willingness to Communicate in Relation to Language Use among Pakistani Undergraduates: A Sociocultural Perspective - Ubaid, Ullah; Joseph, Ramanair; Soubakeavathi, Rethinasamy (Studies in English Language and Education (SiELE), 2022)
This study aimed to investigate English as a second language (ESL) undergraduates’ sociocultural perspective of willingness to communicate (WTC) in English inside the classroom in relation to language use outside the classroom. The participants were 440 ESL undergraduates selected through the cluster sampling method from eight universities in Khyber Pakhtunkhwa Province in Pakistan. The data were collected through questionnaires on WTC in English inside the classroom and language use outside the classroom. The findings revealed that the participants’ level of WTC in English was high for most social interactions within the classroom, such as in groups, during activities, with the same gender, and when given preparation time in groups. The findings for language use showed that a mixture of languages, such as Pashto and Urdu, was predominantly used in the family, neighbourhood and friendship, religion, education, and transaction domains. In contrast, English was primarily used in the mass media and social media domains. Moreover, the findings revealed that WTC in English inside the classroom was positively correlated with social media, mass media, transaction and education domains but negatively correlated with the family domain.